Ferrocene-liposome-PEG: a robust ˙OH/lipid peroxide nano-converter for inducing tumor ferroptosis. (6th December 2022) - Liu, Yang; Chen, Jinzhu; He, Zi; Luo, Huiling; Liu, Xinxin; Sun, Yanan; Ge, Dongtao; Liu, Xin; Shi, Wei
Abstract : A robust ˙OH/LPO nano-converter with high tumor specificity and low systemic side effects enhanced the ferroptosis effect on tumors. Abstract : Ferroptosis induced by iron-dependent accumulation of lipid peroxides (LPOs) has received increasing attention in cancer therapy, especially chemodynamic therapy (CDT). However, the quick annihilation of hydroxyl radicals (˙OH) severely restricts the ˙OH/LPO conversion efficiency, which has become one of the key factors that influences the therapeutic efficacy of ferroptosis-based CDT. Herein, we designed a ˙OH/LPO nano-converter with a high LPO generation efficiency via loading ferrocene (Fc), a green Fenton catalyst, in the phospholipid bilayer of liposome-PEG (Fc-Lp-PEG). Under catalysis with Fc, the over-expressed H2 O2 in tumors can be decomposed to ˙OH. The generated ˙OH in situ reacts with unsaturated lipids on the liposome, and is converted into LPOs, which spread the lipid peroxidation chain reaction to the remote membranes of cells and organelles, triggering efficient cancer cell ferroptosis. Systematic in vitro and in vivo therapeutic outcomes showed the high tumor inhibition ratio (74.0%) and the low side effects of Fc-Lp-PEG on 4T1 tumor-bearing mice. This novel strategy for improving the ˙OH/LPO conversion efficiency might provide new insights for the clinical development of ferroptosis-based CDT.